Potential Controllable Redox Couple for Mild and Efficient Lithium Recovery from Spent Batteries - Chang, Xin; Fan, Min; Yuan, Boheng; Gu, Chao‐Fan; He, Wei‐Huan; Li, Chen; Feng, Xi‐Xi; Xin, Sen; Meng, Qinghai; Wan, Li‐Jun; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2023)
The prosperity of the lithium‐ion battery market is dialectically accompanied by the depletion of corresponding resources and the accumulation of spent batteries. It is an urgent priority to develop green and efficient battery recycling strategies for helping ease resources and environmental pressures at the current stage. Here, we propose a mild and efficient lithium extracting strategy based on potential controllable redox couples. Active lithium in the spent battery without discharging is extracted using a series of tailored aprotic solutions comprised of polycyclic aromatic hydrocarbons and ethers. This ensures a safe yet efficient recycling process with nearly ≈100 % lithium recovery. We further investigate the Li + ‐electron concerted redox reactions and the effect of solvation structure on kinetics during the extraction, and broaden the applicability of the Li‐PAHs solution. This work can stimulate new inspiration for designing novel solutions to meet efficient and sustainable demands in recycling batteries.